Activated IL-23/IL-17 pathway closely correlates with increased Foxp3 expression in livers of chronic hepatitis B patients - Mao Qing; Zhou Jijun; Tian Yi; Huang Zemin; Zheng Yanhua; Wang Qinghong; Wu Yuzhang; Ni Bing (BMC Immunology, 2011)
Abstract Background Foxp3 protein plays a critical role in mediating the inflammatory response and can inhibit the proinflammatory IL-23/IL-17 pathway. However, the molecular interplay of Foxp3 and the IL-23/IL-17 pathway in patients with chronic hepatitis B (CHB) remains unclear. To this end, we analyzed the expression patterns of Foxp3- and IL-23/IL-17 pathway-related proinflammatory cytokines in 39 patients with acute-on-chronic liver failure, 71 patients with CHB and 32 healthy controls. Results Foxp3 expression was found to be elevated in and mainly expressed by the CD4+ T cell sub-population of peripheral blood mononuclear cells and liver tissues of patients with hepatitis B. The intrahepatic expression of Foxp3 strongly correlated with the copies of HBV DNA and the concentration of surface antigen, HBsAg. IL-23/IL-17 pathway-related proinflammatory cytokines were also found to be significantly increased in patients' liver tissues, as compared to healthy controls. Moreover, Foxp3 expression was strikingly correlated with the production of these cytokines in liver tissues of CHB patients. Conclusions The closely-correlated increase of Foxp3 and IL-23/IL-17 pathway activity in HBV-infected livers suggests that the proinflammatory IL-23/IL-17 pathway had not been effectively suppressed by the host immune machinery, such as Treg (Foxp3) cells. Constitutive activation of the IL-23/17 pathway, thus, may support the chronic hepatitis B state.